Dinamika Agama di Era Internet - Cut Asri (CV. Ulil Albab Corp, 2022)
This paper discusses religion in the internet era using the library method by reviewing a number of related publications, whether in the form of journals, scientific articles, books, or other relevant references in obtaining the data. From the exploration carried out by the author regarding religion in the internet era, he found that the internet provides convenience in many ways from human life, both through communication, gaining general knowledge to understanding religion can also be obtained through the internet. Unlimited and actual sources of information can be accessed very quickly via the internet. However, it cannot be denied that knowledge sourced from the internet also gets a shift in understanding because it is in accordance with the way of thinking for each individual. At least, there are three dimensions of change in the field of religion that take place in virtual spaces. First, the dimension of religious institutions that gave birth to online religious institutions. Second, the ritual dimension which is marked by the online religion phenomenon. Third, the literacy dimension which can be seen from the high public interest in seeking information about religion through digital media (religion online).